Improving Student Learning Activities through Brainstorming Learning Method in Civics Class X 7 at Madani Palu Integrated Model State Senior High School - Zulfazri, Zulfazri; Jamaludin, Jamaludin; Etta, Nita Suriyani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to increase student learning activities through the Brainstorming learning method in the Civics Class X 7 subject at SMA Negeri Model Terpadu Madani Palu. The type of research used is classroom action research (PTK) which consists of II cycles. The research design follows the research stages which refer to the Kemmis and McTaggart model, namely: (1) planning stage, (2) implementation stage, (3) observation stage, (4) reflection stage. The subjects of this research were 30 students in class X 7 who took Civics subjects. Data collection techniques in this research were carried out using observation sheets, interviews and documentation. From the results of applying the Brainstorming learning method, the results obtained were able to increase student learning activity from cycle I to cycle II, namely teacher activity was obtained from 50% increasing to 76.66% and was included in the very good category. Based on observations of student activities in cycles I and II, it was found that there had been an increase, initially in cycle I there were still students who got a score of 1 and there were no students who got a score of 4, whereas in cycle II there were no students who got a score of 1 and there were several students who got a score of 1. score 4. And the results of observations of student learning activity indicators in cycle I and cycle II have increased, namely from a percentage of 50% to 100% in the "very good" category.